Communication Skills in Software Engineering: A Multivocal Review - Rabelo, Dannilo; Peres, Deisy; Dias, Emmanuel; Rocha, Thayssa; Freitas, Enne Rebeca de; Gama, Kiev; Pinto, Gustavo (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2026: Anais do XI Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2026)
Communication skills are increasingly recognized as essential in Software Engineering, yet discussions about them remain fragmented across academic and gray literature. This fragmentation is problematic because it limits a broader understanding of how communication is valued, taught, and applied in both educational and professional settings. Through a multivocal literature review, we found strong convergence between academic and gray sources in treating communication as a core competency, while also identifying differences in emphasis, with academia focusing on conceptualization and empirical evidence and gray literature stressing practical consequences and emerging industry practices.